Soft solution synthesis, non-isothermal decomposition kinetics and characterization of manganese dihydrogen phosphate dihydrate Mn(H2PO4)2·2H2O and its thermal transformation products - Boonchom, Banjong; Danvirutai, Chanaiporn; Maensiri, Santi (My University, 2008)
Manganese dihydrogen phosphate dihydrate (Mn(H2PO4)2·2H2O) was synthesized by a simple, rapid and cost-effective method using Mn(c) and H3PO4 in water-acetone medium at ambient temperature. The thermal stability of the Mn(H2PO4)2·2H2O was studied by means of the non-isothermal kinetic (Kissinger method). The specificity of thermal decomposition was characterized by identification of the bonds to be selectively activated due to energy absorption at vibrational level, which was assigned by comparison of the calculated wavenumbers with the observed wavenumbers in FTIR spectra. These results were used to identify the molecules or ions that were eliminated in each thermal transition step. The thermal transformation products from the synthesized Mn(H2PO4)2·2H2O according to the thermal treatments at 243, 773 and 1073 K were obtained to be Mn(H2PO4)2, Mn2P4O12 and Mn2P2O7, respectively. The synthesized Mn(H2PO4)2·2H2O and its thermal transformation products were characterized by scanning electron microscopy (SEM), X-ray powder diffraction (XRD), and FTIR spectroscopy. The SEM micrographs of the obtained products show the different morphologies, which are important for specific applications. © 2007 Elsevier B.V. All rights reserved.
Keywords: Manganese cyclotetrametaphosphate; Manganese dihydrogen phosphate dihydrate; Manganese pyrophosphate; Non-isothermal kinetics; Thermal analysis